2000
DOI: 10.1073/pnas.97.11.6126
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cells differentiate into oligodendrocytes and myelinate in culture and after spinal cord transplantation

Abstract: Demyelination contributes to the loss of function consequent to central nervous system (CNS) injury. Enhanced remyelination through transplantation of myelin-producing cells may offer a pragmatic approach to restoring meaningful neurological function. An unlimited source of cells suitable for such transplantation therapy can be derived from embryonic stem (ES) cells, which are both pluripotent and genetically flexible. In this paper we show that oligodendrocyte cultures can be reliably produced from retinoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
320
1
9

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(339 citation statements)
references
References 51 publications
9
320
1
9
Order By: Relevance
“…Embryonic stem (ES) cells are derived from the inner cell mass of blastocyst-stage embryos, and are pluripotent cells that are able to generate the entire repertoire of cell types in the body. Glial precursors with myelinogenic properties were derived from mouse ES cells [196][197][198]. Human ES cells [199,200] can be directed into neural fate [201,202].…”
Section: Embryonic Stem and Induced Pluripotential Cellsmentioning
confidence: 99%
“…Embryonic stem (ES) cells are derived from the inner cell mass of blastocyst-stage embryos, and are pluripotent cells that are able to generate the entire repertoire of cell types in the body. Glial precursors with myelinogenic properties were derived from mouse ES cells [196][197][198]. Human ES cells [199,200] can be directed into neural fate [201,202].…”
Section: Embryonic Stem and Induced Pluripotential Cellsmentioning
confidence: 99%
“…They also have the advantage of being able to migrate into the surrounding tissues. [61][62][63][64] ESC have also been shown to have the ability to differentiate into oligodendrocytes and myelinate naked axons in culture. The outcome in animal models of SCI is improved by the use of suitable polymer scaffolds within the lesion site designed to provide a framework for the regenerating axons.…”
Section: Stem Cell Experiments On Animal Models Of Neurological Diseasementioning
confidence: 99%
“…ESCs express distinct surface markers, such as Oct-4, Sox-2 and SSEA-1/2/3/4. Several studies identified an ability of such cells to differentiate into myelin-producing cells (oligodendrocytes) [25][26][27][28][29][30][31][32][33] and neurons [34][35][36] therefore, became suitable candidates for neuro-regeneration and remyelination in diseases such as MS. In a recent study it was established that neurospheres derived from ESCs being obtained from ILRIL6 chimeras (soluble IL-6 receptor fused to IL-6) and could exhibit higher differentiation into oligodendrocytes with more branches and peripheral accumulation of myelin-basic protein on myelin membranes [36].…”
Section: Discussionmentioning
confidence: 99%